The influence of neurodynamic mobilization on chronic discogenic sciatica - Shaimaa Mohamed Abdelmageed; Hussein Ahmed Shaker; Mona Abdelmoniem Nada; Moshera Hassan Darwish (Cairo : Shaimaa Mohamed Abdelmageed, 2011)
Sciatica is a common clinical problem causing pain and functional disability . The purpose of this study was to determine the influence of neurodynamic mobilization of sciatic nerve on chronic discogenic sciatica . It can be concluded that suggested neurodynamic techniques are effective methods in treatment of chronic discogenic sciatica
Thesis (M.Sc.) - Cairo University - Faculty of Physical Therapy - Department of Physical Therapy for Neuromuscular and Neurosurgery
Issued also as CD
Keywords: Discogenic sciatica; Lumbar disc prolapsed; Neurodynamic mobilization techniques